2021
DOI: 10.3390/v13091806
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Mutational Events in SARS-CoV-2 Genomes across Brazilian Geographical Regions, February 2020 to June 2021

Abstract: Brazil was considered one of the emerging epicenters of the coronavirus pandemic in 2021, experiencing over 3000 daily deaths caused by the virus at the peak of the second wave. In total, the country had more than 20.8 million confirmed cases of COVID-19, including over 582,764 fatalities. A set of emerging variants arose in the country, some of them posing new challenges for COVID-19 control. The goal of this study was to describe mutational events across samples from Brazilian SARS-CoV-2 sequences publicly o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 34 publications
(42 reference statements)
1
18
2
Order By: Relevance
“…The ongoing pandemic with high mortality and morbidity rates highlights the urgent need for safe and fast development of new pharmaceutics to combat newly emerging viral infections [2,3]. While the ultrafast development of vaccines to fight SARS-CoV-2 has been an unprecedented success story, the high mutation rates leading to rapidly changing viral genomes also require a continuous update of vaccines [4][5][6]. Moreover, antigenic shift, i.e., the recombination of viral genomes and the appearance of new viral subtypes, is a great public health concern [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ongoing pandemic with high mortality and morbidity rates highlights the urgent need for safe and fast development of new pharmaceutics to combat newly emerging viral infections [2,3]. While the ultrafast development of vaccines to fight SARS-CoV-2 has been an unprecedented success story, the high mutation rates leading to rapidly changing viral genomes also require a continuous update of vaccines [4][5][6]. Moreover, antigenic shift, i.e., the recombination of viral genomes and the appearance of new viral subtypes, is a great public health concern [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…While the ultrafast development of vaccines to fight SARS-CoV-2 has been an unprecedented success story, the high mutation rates leading to rapidly changing viral genomes also require a continuous update of vaccines [4][5][6]. Moreover, antigenic shift, i.e., the recombination of viral genomes and the appearance of new viral subtypes, is a great public health concern [5,6]. Thus, antiviral drugs are essential for the management and control of viral infections to fill the gap until virus-specific routine immunization strategies are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, some studies of SARS-CoV-2 at the genomic level were performed aiming at identifying the circulating variants (Candido et al, 2020;Xavier et al, 2020;Botelho-Souza et al, 2021;de Souza et al, 2021;Faria et al, 2021;LaMarcus et al, 2022). In March and April 2020, about 500 samples, mostly from the states of Rio de Janeiro and São Paulo (southeast Brazil), were classified into three distinct clades; lineage B was predominant (Candido et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Paiva et al [2] sequenced 101 strains of SARS-CoV-2 from patients presenting COVID-19 symptoms that reside in Pernambuco and showed multiple introductions followed by the ongoing community spread of SARS-CoV-2 at one of the largest metropolitan areas of Northeast Brazil. In another study, de Souza et al [3] described mutational events across samples from Brazilian SARS-CoV-2 sequences available on Global Initiative on Sharing Avian Influenza Data-EpiCoV (GISAID-EpiCoV) [4] and estimated the number of genomes necessary to report a new variant. The authors also reported that the virus genomic diversity detected in Brazil and Chile in South America was similar to that detected in South Africa and India, and all represent potential hotspots for the generation of new variants, especially when social restrictions are not strictly applied, leading to increased viral circulation.…”
mentioning
confidence: 99%